Pacific Island Women and Contested Sporting Spaces Staking Their Claim - Kanemasu, Yoko (2024)
This book focuses on the variety of strategies developed by women athletes in the Pacific Islands to claim contested sporting spaces - in particular, rugby union, soccer, beach volleyball, recreational sports and exercise - as a prism to explore grassroots women's engagement with heavily entrenched postcolonial (hetero)patriarchy. Based on primary research conducted in Fiji, Samoa, Solomon Islands, and Vanuatu, the book investigates contested sporting spaces as sites of infrapolitics intersected primarily by gender and also by other markers of inequality, including ethnicity, sexuality, class and geopolitics. Contrary to historical and contemporary representations of Pacific Island women as victims of gender injustice, it explores how these athletes and those who support them actively carve out space for their transformative agency. Pacific IslandWomen and Contested Sporting Spaces: Staking Their Claim focuses on a region underexamined by sport or gender studies researchers and will be of key interest to scholars and students in Gender Studies, Sport Studies, Sociology and Pacific Studies as well as sport practitioners and policymakers.